2007
DOI: 10.1002/adic.200790112
|View full text |Cite
|
Sign up to set email alerts
|

Flotation Separation and Flame Atomic Absorption Spectrometric Determination of Trace Amount of Lead in Some Environmental Samples

Abstract: A flotation method based on formation of an ion-associate complex between ferroin and Pb(II)-thiosulfate complex is proposed for the quantitative separation and preconcentration of Pb(II) content in various environmental samples. The flotation process was carried out using a 250-mL aliquot of the aqueous solution at the buffering pH of 8.50 in which the ion-associate complex was floated at the interface of the aqueous/xylene phases. The ion-associate complex was then dissolved in 5 mL of acidic solution of 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The detection limits of analyte ions investigated are superior to those of preconcentration techniques for analyses [26][27][28][29][30][31][32][33][34]. The good features of the proposed coprecipitation method showed that it is a convenient and simple one.…”
Section: Resultsmentioning
confidence: 97%
“…The detection limits of analyte ions investigated are superior to those of preconcentration techniques for analyses [26][27][28][29][30][31][32][33][34]. The good features of the proposed coprecipitation method showed that it is a convenient and simple one.…”
Section: Resultsmentioning
confidence: 97%
“…Preconcentration can solve the above two problems and leads to simplified heavy metal determination [9][10][11][12][13][14]. Solid phase extraction is a universal technique in this respect compared to the conventional liquid extraction [15][16][17][18]. Solid phase extraction is based on the utilization of a major constituent as bonded stationary phase immobilized with different ligand or functional group.…”
Section: Introductionmentioning
confidence: 99%
“…Solid phase extraction is based on the utilization of a major constituent as bonded stationary phase immobilized with different ligand or functional group. The nature of the functional group determines the phase selectivity for metal ion while the regeneration of the phase depends on polymer matrix [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a separation-preconcentration step prior to heavy metal determination is usually necessary since the presence of heavy metals in environmental samples is at low levels. Methods including cloud point extraction, membrane filtration, solvent extraction, solid phase extraction, ion-exchange, solvent sublation, and electroanalytical techniques are widely used to solve these problems [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%